2006
DOI: 10.1258/002367706775404462
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bispectral index values, haemodynamic changes and recovery times during sevoflurane or propofol anaesthesia in rabbits

Abstract: SummaryThe aim of this study was to determine and compare the degree of hypnosis achieved during propofol or sevoflurane anaesthesia in rabbits using bispectral index (BIS), and to evaluate its usefulness as a predictor of both haemodynamic changes during anaesthesia and recovery times. Twenty adult male New Zealand White rabbits, average weight 4.470.4 kg, were used for this study. Animals were randomly allocated to one of two groups with 10 rabbits/group. An electroencephalographic recording was obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 56 publications
1
21
0
2
Order By: Relevance
“…Although developed for human CNS monitoring, the BIS has been successfully used on domestic animals, including horses (Haga and Dolvik 2002), dogs (Greene et al 2003), pigs (Greene et al 2004), and rabbits (Martin-Cancho et al 2006). With the exception of dolphins (Tursiops truncatus; Howard et al 2006), use of the BIS in wildlife has not been reported.…”
mentioning
confidence: 99%
“…Although developed for human CNS monitoring, the BIS has been successfully used on domestic animals, including horses (Haga and Dolvik 2002), dogs (Greene et al 2003), pigs (Greene et al 2004), and rabbits (Martin-Cancho et al 2006). With the exception of dolphins (Tursiops truncatus; Howard et al 2006), use of the BIS in wildlife has not been reported.…”
mentioning
confidence: 99%
“…Experiments were performed on 28 Japanese white rabbits weighing 3.2–3.8 kg. After obtaining IV access in an ear vein, the animals were anesthetized with propofol (8 mg∙kg −1 IV bolus followed by an infusion of 36 mg∙kg −1 ∙h −1 ) [12]. A tracheostomy was performed and their lungs mechanically ventilated with an oxygen-air mixture.…”
Section: Methodsmentioning
confidence: 99%
“…After subcutaneous administration of a total of 1 ml lignocaine 1%, four scalp‐needle electrodes were placed in a configuration previously described for EEG monitoring in rabbits [11]. One electrode was placed 2 cm caudal to the lateral canthus of each eye, one reference electrode was placed in the midline overlying the frontal bone, and the ground electrode was placed 2 cm to the left of the central electrode.…”
Section: Methodsmentioning
confidence: 99%